2012
DOI: 10.1007/s00167-012-2239-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of vitamin K2 in subchondral bone in osteoarthritic knee joints

Abstract: This study suggested that vitamin K2 might affect bone turnover since medial condyles showing advanced OA had lower vitamin K2 levels, while lateral condyles showing less advanced OA contained more vitamin K2. Gender and age were not correlated with vitamin K2 localization. All cases had Grade IV OA, and this study suggested that OA grade might be important in controlling the vitamin K2 levels in human bones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Our results showing a relation between GRP and MGP ␥-carboxylation deficiency and OA are also in agreement with recent findings, suggesting that vitamin K metabolism may be associated with synovitis in OA patients, and that serum undercarboxylated OC could be a biomarker for OA [38]. The novel association of both phylloquinone (vitamin K1) and menaquinone (vitamin K2) deficiency with the disease further suggests the use of vitamin K as a potential therapeutic/prophylactic agent for OA [39]. We are currently collecting a representative number of OA patients and controls sera samples to determine and compare levels of (i) vitamin K1 and K2 and (ii) c/uc GRP protein forms, for which we are developing an ELISA detection kit (industrial application reported in the international patent request PCT/PT2009000046).…”
Section: Discussionsupporting
confidence: 92%
“…Our results showing a relation between GRP and MGP ␥-carboxylation deficiency and OA are also in agreement with recent findings, suggesting that vitamin K metabolism may be associated with synovitis in OA patients, and that serum undercarboxylated OC could be a biomarker for OA [38]. The novel association of both phylloquinone (vitamin K1) and menaquinone (vitamin K2) deficiency with the disease further suggests the use of vitamin K as a potential therapeutic/prophylactic agent for OA [39]. We are currently collecting a representative number of OA patients and controls sera samples to determine and compare levels of (i) vitamin K1 and K2 and (ii) c/uc GRP protein forms, for which we are developing an ELISA detection kit (industrial application reported in the international patent request PCT/PT2009000046).…”
Section: Discussionsupporting
confidence: 92%
“…[50] Radiographic OA significantly decreased with increased serum levels of vitamin K. A more recent study provided more evidence of vitamin K, as direct measurements of vitamin K2 in the condyles of knees showed that patients with advanced OA had lower levels of vitamin K2. [51] The authors suggested that this provides evidence for the role in which vitamin K may affect bone turnover. [51] However, other studies have shown that vitamin K supplementation does not provide a protective effect on the severity of OA.…”
Section: Dietmentioning
confidence: 99%
“…[51] The authors suggested that this provides evidence for the role in which vitamin K may affect bone turnover. [51] However, other studies have shown that vitamin K supplementation does not provide a protective effect on the severity of OA. [2] Occupation An individual's occupation may predispose him/her to developing OA.…”
Section: Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study did not include carboxylation as part of the variables. Ishii et al [30] reported that menaquinone level was significantly higher in the femoral/tibial lateral condyles, compared to medial condyles among patients (n = 58; mean age 73 ± 8 years) with Kellgren-Lawrence (KL) grade 4 undergoing total knee arthroplasty, regardless of age and sex. This observation was possibly contributed by the more severe OA condition at the medial condyles, compared to the lateral side.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%